PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP NET PROFIT MARGIN PADA PT INDOFARMA TBK PERIODE 2013-2022 - Seli Nofita Setiani; Siti Nurcahayati (Journal of Research and Publication Innovation, 2024)
This study aims to examine the effect of Current Ratio (X1) and Debt to Equity Ratio (X2) on Net Profit Margin (Y) at PT Indofarma Tbk for the period 2013-2022 partially and simultaneously. The research method used is quantitative method with descriptive analysis techniques which include classical assumption test, multiple linear regression analysis, hypothesis testing and determination coefficient test. The data used is secondary data in the form of financial statements of PT Indofarma Tbk from 2013-2022. The data was tested using the Statistical Product Service and Solution (SPSS) version 25 programme. Based on hypothesis testing with the t test, Current Ratio (CR) has no partial effect on Net Profit Margin (NPM) with a tcount value of 1.404 < t table 2.365 and a significance value of 0.203 < 0.05. While Debt to Equity Ratio (DER) has a partial effect on Net Profit Margin (NPM) with a tcount value of -12.029> t table 2.365 and a significance level of 0.000 <0.05. Simultaneous testing through the f test shows the Fcount value of 107.246> Ftable 4.74 and a significance value of 0.000 <0.05, which means that the Current Ratio (CR) and Debt to Equity Ratio (DER) simultaneously (together) affect Net Profit Margin (NPM) with a coefficient of determination of 96.8% and the remaining 3.2% is influenced by other variables not tested in this study.